Solid-core fiber with ultra-wide bandwidth transmission window due to inhibited coupling. - Grujic, T; Kuhlmey, B; Argyros, A; Coen, S; de Sterke, C (Optical Society of American (OSA), 2010)
We experimentally demonstrate solid-core photonic crystal fibers that guide via the inhibited coupling mechanism. We measure an overall transmission window of more than an octave, as well as an uninterrupted width of almost one octave. The fiber is fabricated in polymer, with high-index ring-shaped inclusions. This type of fiber was conceived based on a simple model which shows that the cutoffs of the modes of a thin ring cluster around the cutoffs of planar waveguide modes. The model shows that such ring based fibers are closely related to kagome and square lattice hollow core fibers, and have transmission bandwidths that could in principle reach 1.6 octaves. Measured transmission properties are in good agreement with rigorous modelling.